2017
DOI: 10.1111/pbi.12725
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐responsive ERFs involved in postdeastringency softening of persimmon fruit

Abstract: SummaryRemoval of astringency by endogenously formed acetaldehyde, achieved by postharvest anaerobic treatment, is of critical importance for many types of persimmon fruit. Although an anaerobic environment accelerates de‐astringency, it also has the deleterious effect of promoting excessive softening, reducing shelf life and marketability. Some hypoxia‐responsive ethylene response factors (ERFs) participate in anaerobic de‐astringency, but their role in accelerated softening was unclear. Undesirable rapid sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 62 publications
1
43
0
Order By: Relevance
“…The above-mentioned regulatory effects of DkNAC7 on deastringency related genes encouraged us to study the response of DkNAC7 to deastringency treatment. From previous results, AHCA treatment (also called CO 2 treatment or high CO 2 treatment: 95% CO 2 and 1% O 2 ) was very effective in removing astringency in various persimmon [ 5 , 7 , 21 ]. Therefore, using previously described materials [ 21 ], the expression of DkNAC7 was analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The above-mentioned regulatory effects of DkNAC7 on deastringency related genes encouraged us to study the response of DkNAC7 to deastringency treatment. From previous results, AHCA treatment (also called CO 2 treatment or high CO 2 treatment: 95% CO 2 and 1% O 2 ) was very effective in removing astringency in various persimmon [ 5 , 7 , 21 ]. Therefore, using previously described materials [ 21 ], the expression of DkNAC7 was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…From previous results, AHCA treatment (also called CO 2 treatment or high CO 2 treatment: 95% CO 2 and 1% O 2 ) was very effective in removing astringency in various persimmon [ 5 , 7 , 21 ]. Therefore, using previously described materials [ 21 ], the expression of DkNAC7 was analyzed. The DkNAC7 gene exhibited a sharp increase in expression in response to AHCA treatment, with the highest level at 1 d ( Fig 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the expression of CWDE is ethylene-dependent; therefore, fruit softening and cell wall disassembly are regulated by ethylene in Charentais melon (Nishiyama et al, 2007). The ERF DkERFs in persimmon fruit was found to directly bind to the promoter of a CWDE gene DkXTH9 and regulate its gene expression (Wang et al, 2017). Therefore, the role of H 2 S in regulating fruit softening could be as a linear signaling pathway (H 2 S-ethylene-CWDE).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Meitha et al identified three ERF-VIIs in grape berries, which are substrates for oxygen-dependent N-end rule proteolysis as in Arabidopsis [81]. Additionally, several hypoxia-responsive ERFs were shown to be directly involved in transcriptional regulation of anaerobic metabolism genes involved in persimmon deastringency [82,83,84]; however, their possible oxygen-dependent regulation via the N-end rule pathway is still unknown. Although it is worth noting that DkERF10, based on an amino acid sequence, could be a candidate substrate of the N-end rule pathway of protein degradation.…”
Section: Activation Of the Anaerobic Response By The N-end Rule Pamentioning
confidence: 99%